Techno‐economic analysis of hemicellulose extraction from different types of lignocellulosic feedstocks and strategies for cost optimization. (18th November 2019) - Geng, Wenhui; Venditti, Richard A.; Pawlak, Joel J.; De Assis, Tiago; Gonzalez, Ronalds W.; Phillips, Richard B.; Chang, Hou‐min
Abstract: Hemicellulose is a polymer found abundantly in lignocellulosic feedstocks, with many potential market applications. However, there has yet to be a large‐scale commercial process to isolate hemicellulose from lignocellulosic biomass. A techno‐economic assessment for hemicellulose extraction from sugarcane bagasse, switchgrass, and poplar was made. Two isolation processes after alkaline extraction were considered: (1) producing total hemicellulose and (2) producing hemicellulose A (water‐insoluble fraction) only. In a greenfield scenario, a byproduct of the process is sugar, whereas in a co‐location scenario the biomass after hemicellulose extraction is returned to the pulp mill for its fiber value. Operating costs, capital investment, minimum hemicellulose selling price (MHSP), the effect of input material and product prices along with several other process parameters on the MHSP were determined for each scenario. Co‐location scenarios had a dramatically lower capital cost and MHSP relative to greenfield scenarios. This was due to co‐location scenarios utilizing existing biomass processing and utilities equipment and not requiring a sugar‐production process. Among the three biomasses, hemicellulose extraction from sugarcane bagasse had the lowest MHSP for all scenarios, mainly due to a higher hemicellulose extraction yield. Extraction of hemicellulose A from sugarcane bagasse in a co‐location scenario had a low capital cost of 56 million USD and had a reasonable MHSP of 274 USD/t (metric ton). This research indicates that there is reasonable economic potential for hemicellulose extraction from lignocellulosic biomass for applications to replace starch or as a starting material for the production of xylo‐oligomeric prebiotics. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd